Adsorption of γ-Valerolactone: An Alternative for Solvent Recovery after Conversion of Lignocellulosic Biomass to Fermentable Sugars - L. G. Coelho; G. Johann; F. Palú; M. G. A. Vieira; R. Guirardello; V. N. T. Júnior; E. A. D. Silva (Chemical and Biochemical Engineering Quarterly, 2022)
The γ-valerolactone is an effective solvent in solubilizing lignocellulosic biomass fractions, although it inhibits microbial activity. To avoid the negative effects on the metabolism of microorganisms, even small quantities of γ-valerolactone need to be removed. This study examined the adsorption of γ-valerolactone on the commercial resin. The removal efficiency, adsorption equilibrium, pH effects, and fixed-bed column conditions were investigated. The highest removal efficiency of γ-valerolactone from sugar solution was 39.92 %, with 413.78 mg g−1 γ-valerolactone adsorption capacity, observed with commercial resin Dowex Optipore L-493 and pH 4.00. Dual-site Langmuir adsorption isotherm was found to be the best-fitting model for describing the adsorption mechanisms of γ-valerolactone on commercial resin. Thus, this study shows that γ-valerolactone could be removed from sugar solution by adsorption on commercial resin. In addition, the process is a viable alternative for the recovery of solvent and keeping the microbial activity in lignocellulosic biomass fractions.